Fatty acid breakdown in developing embryos of Brassica napus L. (December 2000) - Chia, T.; Rawsthorne, S.
Abstract : Developing Brassica napus embryos are primarily concerned with the accumulation of storage products, namely oil, starch and protein. The presence of fatty acid catabolic pathways in the background of this biosynthetic activity was investigated. Enzymes involved in the process of lipid mobilization, such as malate synthase and isocitrate lyase, are detectable towards the late stages of embryo development. [ 14 C]Acetate feeding experiments also reveal that fatty acid catabolism becomes increasingly functional as the embryo matures.